Mahkamah Konstitusi Sebagai Positive Legislator dalam Putusan Nomor 90/PUU-XXI/2023: Perspektif Fiqh Siyasah - Salma Khairunnisa; Frenki; Fikri, Arif (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Decision of the Constitutional Court Number 90/PUU-XXI/2023 has generated significant debate because the Court not only reviewed the constitutionality of Article 169 letter q of Law Number 7 of 2017 on General Elections but also created a new legal norm by acting as a positive legislator. This study aims to analyze the constitutional limits of the Court’s positive legislator function and to assess its implications for constitutionalism and the principles of siyāsah dusturiyyah. This research employs a normative legal method with a library-based approach, examining statutory regulations, Constitutional Court decisions, and constitutional law literature, complemented by the perspective of fiqh siyāsah. The findings indicate that the Constitutional Court exceeded its constitutional authority by introducing a new legal norm that should fall within the legislative domain. The decision fails to meet the standards of procedural and moral justice, as reflected in indications of conflicts of interest, weaknesses in the petitioner’s legal standing, and inconsistencies with the Court’s previous rulings. These results demonstrate that the application of the positive legislator doctrine in this case is inconsistent with the principle of al-‘adl in siyāsah dusturiyyah and has the potential to undermine constitutional supremacy.